Complete response of advanced esophageal squamous cell carcinoma with first-line chemotherapy combined with immunotherapy: a Case report - Wei, Yahong; Han, Shaohui; Shi, Yabin; Li, Yaxing; Zhang, Qi; Zhang, Lijuan; Cheng, Yan; Yan, Xiaolu; Jia, Yitao (Frontiers in Immunology, 2025)
Esophageal squamous cell carcinoma (ESCC) is a prevalent and aggressive malignancy, often diagnosed at an advanced stage with poor prognosis. This case report highlights the successful treatment of a patient with advanced ESCC, who presented with bilateral lung and adrenal gland metastases. Despite the aggressive nature of the disease, the patient underwent a regimen of first-line chemotherapy combined with immunotherapy, followed by immune maintenance therapy. Remarkably, the patient achieved complete remission after the completion of treatment, demonstrating the potential efficacy of this combined therapeutic approach in managing advanced ESCC with multiple metastatic sites.